Financial Literacy and Financial Performance of Small and Medium-sized Enterprises - Yakob, Sajiah; Yakob, Rubayah; B.A.M., Hafizuddin-Syah; Rusli, Roslida Zalila Ahmad (The South East Asian Journal of Management, 2021)
Research Aims: The study aims to examine the influence of financial literacy on the performance of small and medium-sized enterprises (SMEs) in Malaysia. Design/methodology/approach: The data were obtained from questionnaires distributed to 200 SME managers/owners. Multiple regression analysis was applied to test the influence of financial literacy on SMEs performance by controlling manager profile and SME-specific characteristics. Research Findings: Multiple regression results prove that financial literacy has a positive and significant impact on SMEs' performance. Managers/owners with financial literacy skills understand business-related financial concepts, including debt, savings, takaful, insurance, and investment, which ensure the good performance of their business. Theoretical Contribution/Originality: Similar research has been conducted outside Malaysia. However, there is a need to validate the financial literacy and SME performance relationship in the Malaysian environment due to differences in culture; ways of thinking; and legal, business, and political situations. These differences lead to different responses which then contribute to the way the effect of financial literacy on SME performance is explained. In addition, this study improves the consistency of the existing evidence on SME performance and expands the scope of the Resource-Based View (RBV) from the perspective of SMEs Research limitation & implications: Government agencies such as SME Corporation recognise the importance of financial literacy among entrepreneurs. Therefore, proactive efforts need to be accelerated to provide an adequate level of financial literacy among entrepreneurs. Furthermore, entrepreneurial finance can be introduced in formal and non-formal education to ensure that every layer of society enjoys the benefits regardless of their economic status.